Unconstrained facial recognition systems: a review - Hassan, Marwa Yousif; Khalifa, Othman Omran; Abu Talib, Azhar; Hassan Abdalla Hashim, Aisha (Asian Journal of Applied Sciences, 2015)

(untitled)
Face recognition presents a challenging problem in the field of image analysis and computer vision, and as such has received a great deal of attention over the last few years because of its applications in various domains. Face recognition under controlled environment that is where pose, illumination and other factors are controlled, has well been developed in the literature and near perfection accuracy results have been achieved. However, the unconstrained counterpart, where these factors are not controlled, still under heavy research. Recently, newly developed algorithms in the field that are based on deep learning technology have made significant progress. In this paper, an overview of the newly developed unconstrained facial recognition systems is presented.